Impairment of reproductive capabilities in three subsequent generations of asymmetric hybrids between Eisenia andrei and E. fetida from French, Hungarian and Polish laboratory colonies. - Barbara Plytycz; Janusz Bigaj; Aleksandra Rysiewska; Artur Osikowski; Sebastian Hofman; Agnieszka Podolak; Pawel Grzmil (PLoS ONE)
Eisenia andrei (Ea) and E. fetida (Ef) lumbricid earthworms are simultaneous hermaphrodites potentially capable of self-fertilization and hybridization. We have shown previously that reproductive isolation in these species is incomplete in Ea and Ef earthworms of French provenance, as viable offspring appeared in inter-specific pairs. Fertile asymmetric hybrids developed from Ea-derived ova fertilized by Ef-derived spermatozoa, as well as Ea or Ef specimens derived after self-fertilization (resulting from admixture of endogenously produced spermatozoa with sperm from a partner), but never Ef-hybrids from Ef-ova fertilized by Ea-spermatozoa. The latter appeared only in backcrosses of Ea-hybrids with the Ef. Here we show that these phenomena are not unique for French Ea/Ef earthworms, but are shared by earthworms from French, Hungarian, and Polish laboratory cultures. Semi-quantitative studies on fertility of Ea-derived hybrids revealed gradually decreasing numbers of offspring in three successive generations, more rapid in backcrosses with Ef than with Ea, and the absence of progeny in pairs of hybrids, despite the presence of cocoons in almost all pairs. Based on species specific mitochondrial and nuclear DNA sequences, we provide the first examples of two unique sterile hybrids with mitonuclear mismatch and potential mitonuclear incompatibility among offspring of one of the hybrid+Ef pairs. Earthworms from the investigated populations did not reproduce when kept from hatching in isolation or with representatives of Dendrobaena veneta but started reproducing upon recognition of a related partner, such as Ea, Ef or their hybrids. The existence of Ea or Ef specimens among offspring of hybrid+Ea/Ef pairs might be explained either by partner-induced self-fertilization of Ea/Ef or hybrid-derived ova, or by cross-fertilization of Ea/Ef /hybrid ova by partner-derived spermatozoa; the latter might contribute to interspecific gene introgression.